Differential capacitance of ionic liquid and mixture with organic solvent. (20th January 2021) - Gu, Chunyi; Yin, Li; Li, Shu; Zhang, Bohai; Liu, Xiaohong; Yan, Tianying
Abstract: Understanding of electric double layer (EDL) is the cornerstone for the development of ionic liquids (ILs)-based EDL capacitors. Differential capacitance ( Cd ) is a key physical quantity to understand the EDL at electrode/ILs interfaces. In this work, we study the capacitance properties of 1-ethyl-3-methyl-imidazolium bis(trifluoromethanesulfonyl)imide (EMIM + /TFSI − ) and its mixture with 50 mol% 1, 2-dimethoxyethane (DME) on glassy carbon electrode by electrochemical impedance spectroscopy (EIS). The EIS spectrum shows both fast and slow capacitance processes, and Cd is attributed to the fast Debye process by fitting the full EIS spectrum. The Cd curve switches from bell-shape for neat IL to camel-shape for 50 mol% EMIM + /TFSI − /DME mixture, with much higher Cd over the whole electrochemical window for the latter. The measured Cd was further fitted by a mean-field theory ( Phys. Chem. Chem. Phys. 20 (2018) 17606–17614). Using the mean-field theory, we suggest that the higher Cd is caused by the reduced effective EDL screening length, which results from the reduced overscreening effect due to the weakened ionic correlations on adding DME.